MENGENAL PENTINGNYA KESEHATAN MENTAL: DAMPAK BUNUH DIRI DAN GEJALA GANGGUAN KESEHATAN MENTAL - Nabila Sarah Setiawan; Iwan Setiawan (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research discusses the significance of mental health with a focus on the impact of suicide and the symptoms of mental health disorders. It also investigates the relationship between poor mental health and suicide rates, presenting empirical findings that illustrate the psychological, social and well-being impacts on individuals. In addition, this study identified symptoms common to mental health disorders, and provided an in-depth understanding of the manifestations of conditions such as depression, anxiety, and social distress. The knowledge gained from this research can serve as a basis for the development of more effective interventions and policies to improve the overall mental health of the community. The research method used was literature review. Results obtained of this study are efforts to reduce the social stigma surrounding mental health issues that are closely tied to the mental health issues that are closely tied to the impact of suicide and symptoms on mental health.